Civil Rights Procedural Problems - Carl Tobias (Washington University Law Quarterly, 1992)
The article initially examines procedural developments that have detrimentally affected civil rights plaintiffs over the last decade and a half. The piece then analyzes the Civil Rights Act of 1991, emphasizing how that measure fails to remedy numerous procedural complications which confront these plaintiffs. Accordingly, the essay affords suggestions for additional change that would respond to the procedural difficulties which remain.
Keywords: Civil procedure; Discrimination in employment